A pilot study for an innovative approach highlighting Actin and COI mRNAs as potential biomarkers of quality of the edible crustacean Nephrops norvegicus (Linnaeus, 1758). (March 2019) - Costa, Caterina; Pinsino, Annalisa; Bonaventura, Rosa; Russo, Roberta; Zito, Francesca; Matranga, Valeria
Abstract: Widely appreciated in gastronomy, many harvested and farmed Crustacean species are a great economic resource in the fishery business, throughout the world. Factors like pollutants and/or improper management in on-board/on-shore practices may adversely affect their edible quality and shelf-life. Recent studies from applied scientific research have been supporting the fishing industry and trading companies, in order to improve post-harvest practices and offer a safe and competitive product of high quality. Here, we developed an innovative molecular approach to get basic information on crustacean quality by using the European lobster Nephrops norvegicus (Linnaeus, 1758). For the first time, we investigated muscle-exudates of thawed lobsters for the presence of nucleic acids and analysed mRNA targets selected at NCBI to test their potential use as biomarkers of quality in frozen-thawed seafood. By RT-PCRs and sequencing we validated small amplicons of Actin, Cytochrome oxidase subunit 1 (COI), Calpain M, Prophenoloxidase (ppo) and Crustin-like antimicrobial peptide. In comparative One Step RT-PCR and/or One Step RT- q PCR assays, we analysed their amplification profiles at 1, 4 and 7 days after thawing (a.t.), in lobsters maintained to checked temperatures from capture. Based on amplification efficiency (AE), inversely correlated to the time after thawing and loss of RNA targets integrity, we identified new highly sensitive, species specific early indicators of quality. Our results highlight the advantage of using amplicons from exudates in different food science applications including authenticity/traceability, and provide new insights for the development of scientific tools applicable to crustacean quality monitoring on industrial-scale. Highlights: Molecular changes detect the quality of the edible lobster of high economic impact. RNA targets of lobster with known temperature histories show different profiles. RNA integrity of biomarkers of quality declines in the days after thawing at 4 °C. Two biomarkers of quality show high amplification efficiency in preserved lobsters. The new nucleic acid source can be useful for other food science purposes.